Hetero-oligomerizaciòn entre los receptores Mas de Angiotensina-(1-7) y B2 de Bradikinina : consecuencias funcionales - Cerrato, Bruno Diego (2018)
Bradykinin (BK) B2 receptor (R) and angiotensin (Ang) (1-7) MasR-mediated effects are physiologically interconnected. The molecular basis for such cross-talk is unknown. We investigated B2R-MasR heteromerization and its functional consequences. B2R fused to the cyan fluorescent protein and MasR fused to the yellow fluorescent protein were co-expressed in HEK293T cells. Fluorescence resonance energy transfer (FRET) analysis showed that B2R and MasR formed a constitutive heteromer which was not modified by their agonists but was decreased by the antagonists suggesting heteromer dissociation. B2R-MasR heteromerization induced an increase in the MasR ligand binding affinity. Upon agonist stimulation, the heteromer was internalized with a slower sequestration rate from the plasma membrane compared to the single Rs. Concerning Akt activity, a significant BK promoted activation was detected in B2R-MasR- but not in B2R-expressing cells. Ang-(1-7) and BK elicited anti-proliferative effects only in cells expressing B2R-MasR heteromers but not in cells expressing each R alone. Proximity ligarion assay confirmed B2R-MasR interaction in human glomerular endothelial cells supporting the interaction between both Rs in vivo. Our findings provide an explanation for the cross-talk between BK B2R and Ang-(1-7) MasR mediated effects. B2R-MasR heteromerization induces functional changes in the R that may lead to long-lasting protective properties.